COMMUNICATION STRATEGY OF SEDULUR SIKEP SAMIN’S BELIEVERS IN BUILDING POSITIVE IMAGE IN COMMUNITY - Robih Muzhaffar Nasri (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Negative images were commonly experienced by minority groups in society, including Sedulur Sikep Samin’s believers. Therefore, a communication strategy was needed to build a positive image in society. This study aimed to determine the communication strategy of Sedulur Sikep Samin’s believers in Larikrejo Village, Undaan District, Kudus Regency, Central Java in building a positive image in society. This research explored three elements of communication strategy, namely message planning, communication approach, and media selection. This study used the Co-Cultural theory of Mark Orbe. Interpretive phenomenological analysis was used in this study as a technical data analysis. The results of this study indicated that Sedulur Sikep Samin’s believers in Larikrejo Village use accommodation strategies to build a positive image in society. This strategy included non-assertive and assertive accommodation. In terms of planning the message of Sedulur Sikep Samin’s believers, they conducted deliberation first before the message was conveyed to the public. The communication approach was carried out by mingling, staying in touch, tying brotherhood both verbally and non-verbally to society and local government. This approach was in accordance with the ancestral teachings of Sedulur Sikep Samin’s which had been passed down from generation to generation (Samin Teachings). In terms of media selection, Sedulur Sikep Samin’s believers used outdoor media such as signposts, banners, photos, and posters displayed in the secretariat office.